PERANAN TENAGA KERJA, MODAL, DAN TEKNOLOGI TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT NELAYAN DI DESA - Revan Ilyaza; Nasikh Nasikh (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2022)
The income of fishing communities is still an unresolved polemic. The income of fishermen is largely determined by the level of catch. When the catch rate is high, fishermen can get a bigger income. The facts today still show that the catch rate by fishermen is still very low. So the income received is very small. When this continues, do not ever expect that the fishing community can become a society whose class of life can increase. This study aims to explain the role of labor, capital, and technology in increasing the income of fishermen in the village. This research is a literature study (Library Research). In this research literature study examines articles and scientific journals related to the variables to be studied, namely labor, capital, technology, and fishermen's income. The data collection technique used is the documentation technique. The data analysis technique used is the method of content analysis (Content Analysis). The results showed that labor, capital, and technology are factors that have a role in increasing the income of fishing communities in the village. When fishermen have a large workforce, large capital, and are able to use catch technology appropriately, it is possible to get more catches, thus affecting the increase in fishermen's income in the village.